Circular Structures of Puffer Fish: A New Metaheuristic Optimization Algorithm - Catalbas, Mehmet Cem; Gulten, Arif (Ieee, 2018)
In this paper, we presented a new metaheuristic optimization algorithm which we named as circular structures of puffer fish. This algorithm has been inspired by the behaviors of male puffer fish for charming the female ones. The special type of male puffer fishes, Torquigener albomaculosus, has a special ability to build a unique circular structure on the seabed. The building process of a circular structure consists of several regular sub-dimensions and as the result of this process, a circular structure is constructed. The water flow rate at the center of this structure is reduced. Additionally, these structures have some numerical properties such as the ratio of inner and outer circular structures diameter or the number of peaks on the structure. The results of the proposed algorithm are compared with genetic algorithm through various performance criteria. The most popular performance analyzing functions were used in the optimization of the algorithm performance comparison process.
3rd International Conference on Electrical and Biomedical Engineering, Clean Energy and Green Computing (EBECEGC) -- APR 25-27, 2018 -- Lebanese Univ, Fac Engn, Beirut, LEBANON
Keywords: component; optimization problem; metaheuristic algorithm; bio-inspired algorithms; genetic algorithm; adaptive search